Preschool children with attention deficit hyperactivity disorder (ADHD) in inclusive settings: Challenging but not problematic. - Saad, Supiah (Universiti Pertanian Malaysia Press, 2010)
This paper describes mainstream preschool teachers’ perceptions and attitudes towards students exhibiting Attention Deficit Hyperactivity Disorder ADHD characteristics. An ADHD checklist (ADHDC), specially developed for studying Malaysian preschool children with ADHD, was used in screening children with ADHD-like behaviours. Based on teachers’ rating on the ADHDC, ten children from eight different preschool classrooms were chosen from eight different schools: four schools in the rural areas and four in the urban areas. All the eight teachers who were involved in the rating process became samples for exploring their perceptions and attitudes towards students with ADHD. Classroom observations and interviews were used as methods for gathering information. The results showed that all the ten selected children exhibited core features of ADHD symptoms, either inattentiveness or hyperactivity/impulsiveness or both, as rated by their teachers. In general, the teachers’ perceptions and attitudes were positive towards these ADHD children’s conditions.